TRENDS OF DENGUE HEMORRHAGIC FEVER IN BAU BAU DISTRICT, SOUTHEAST SULAWESI PROVINCE, INDONESIA, 2009-2014 - Ramadhan Tosepu (Public Health of Indonesia, 2017)
Objectives: To analyze trends of dengue hemorrhagic fever in Baubau district from 2009 to 2014